Analisis Faktor Domestik Amerika Serikat dalam Mengambil Kebijakan The Cuban Thaw 2014 - Wailanduw, Gilbert Leonard; Kumala Dewi, Putu Ratih; Parameswari, A.A Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 2 No 2 (2023): Jurnal DIKSHI, 2023)
This research aims to describe the national interest in the US economy, focusing on domestic factors through The Cuban Thaw 2014. The separation between the two countries (1961-2014) has become the reason for the US to normalize relations with Cuba. This research used a qualitative descriptive approach in conjunction with a national interest framework that focuses on foreign policy, with domestic variables as the primary focus of the analysis. This research concluded that there were several reasons as to what the US domestic factors, including natural resources such as oil, agriculture, and foods; jobs; telecommunication; tourism; public opinion; electoral cycles; and the impact of negotiations relating to the two countries through two-level games. The US economy in 2014-2016 has significantly changed, that can be seen from four economic indicators, US GDP, US unemployment rate, US net investment in nonfinancial assets, and US exports of goods and services.